Distributed Leadership Practice in Swiss "Eco-Schools" and Its Influence on School Improvement. Issue 4 (1st October 2020) - Zala-Mezö, Enikö; Bormann, Inka; Strauss, Nina-Cathrin; Müller-Kuhn, Daniela
ABSTRACT: In this paper we connect the concepts of distributed leadership (DL) and educational change by asking: How do different practices of DL relate to change in schools? We answer this question by studying 12 schools in Switzerland during the implementation of the "Education for Sustainable Development" concept. In an embedded mixed methods design we analyzed semi-structured interviews and used an online survey where all school members assessed change processes in their school. We found that the leadership strategy within schools appears to align with the quality of change: the more efficient the leadership strategy, the more the perceived change.